Nuclear spin effects in semiconductor quantum dots - Chekhovich, E. A.; Makhonin, M. N.; Tartakovskii, A. I.; Yacoby, A.; Bluhm, H.; Nowack, K. C.; Vandersypen, L. M. K. (Nature materials, 2013)
Semiconducting quantum dots are considered candidate materials for realizing spin-based quantum computation devices. This Review examines the main results obtained over the past decade concerning the so-called central spin problem, namely the interaction between a single electronic spin or hole with the surrounding nuclear environment. The interaction of an electronic spin with its nuclear environment, an issue known as the central spin problem, has been the subject of considerable attention due to its relevance for spin-based quantum computation using semiconductor quantum dots. Independent control of the nuclear spin bath using nuclear magnetic resonance techniques and dynamic nuclear polarization using the central spin itself offer unique possibilities for manipulating the nuclear bath with significant consequences for the coherence and controlled manipulation of the central spin. Here we review some of the recent optical and transport experiments that have explored this central spin problem using semiconductor quantum dots. We focus on the interaction between 10 4 –10 6 nuclear spins and a spin of a single electron or valence-band hole. We also review the experimental techniques as well as the key theoretical ideas and the implications for quantum information science.